Water encyclopedia - Lehr, Jay H., 1936-; Keeley, J. W.; Lehr, Janet K.; Kingery, Thomas B. (John Wiley & Sons, 2005)
Comprehensive resource of information relating to the scientific and technological aspects of water. Covers the role of water in science, engineering and society.